The role of science and technology in human development - Timur Shamshetov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article discusses the importance of science and technology in human development and the role of knowledge in people’s lives. The advancement of science and its connection for humanity is essential.